Kinetics of the inhibition of plasminogen activators by the plasminogen-activator inhibitor. Evidence for 'second-site' interactions. - Chmielewska, J (1988)
The reactions between plasminogen-activator inhibitor (PAI) and different plasminogen activators were studied in the presence of chromogenic peptide substrates for the enzymes. Our findings suggest that the rate constants for the reactions of PAI with single-chain tissue plasminogen activator (tPA), two-chain tPA, high-Mr urokinase and low-Mr urokinase are high and quite similar (1.6 X 10(7)-3.9 X 10(7) M-1.s-1). A free active site in the enzymes seems to be necessary for their reaction with PAI. Amino acids with antifibrinolytic properties did not interfere with the reactions. However, di-isopropyl phosphorofluoridate-inactivated tPA inhibited the reaction between PAI and all plasminogen activators in a similar way. These findings clearly demonstrated that a 'second-site' interaction, in addition to that between the enzyme active site and the inhibitor 'bait' peptide bond, is of importance for the high reaction rate. The reaction rate between PAI and single-chain tPA in the presence of an activator substrate (D-Ile-Pro-Arg p-nitroanilide) was decreased in the presence of fibrin. Fibrin caused a decrease in the Km for the single-chain tPA-substrate reaction. As a consequence, the 'free' concentration of single-chain tPA in the system decreased in the presence of fibrin, affecting the reaction rate between PAI and single-chain tPA. The phenomenon might be of physiological relevance, in the sense that single-chain tPA bound to fibrin in the presence of plasminogen would be protected against inactivation by PAI.